Green waste recycling of peanuts highly contaminated with aflatoxins in clay brick manufacturing - El-Mekkawi, Samar A. (2023)
The safe disposal of green waste is necessary for a clean environment, with the safe disposal of waste contaminated with aflatoxins being of particular importance. This work presents a novel route for utilizing contaminated grains in the production of clay bricks. In this work, the contaminated peanut (P) with aflatoxins (AFs) is divided into two categories: PA is the contaminated peanut kernel (without the outer shell), and PB is contaminated whole peanut grain (with the outer shell). Both of ground PA and PB were used to replace the clay in fired building bricks. The raw materials were characterized using X-ray fluorescence (XRF), X-ray diffraction (XRD), and thermo-gravimetric analyses (TGA). The effectiveness of this approach was evaluated by measuring the effect of the replacement percentage and firing temperature on the properties of the produced building bricks.